2013
DOI: 10.1088/0004-637x/772/1/73
|View full text |Cite
|
Sign up to set email alerts
|

GRB 090727 and Gamma-Ray Bursts With Early-Time Optical Emission

Abstract: We present a multi-wavelength analysis of gamma-ray burst GRB 090727, for which optical emission was detected during the prompt gamma-ray emission by the 2-m autonomous robotic Liverpool Telescope and subsequently monitored for a further two days with the Liverpool and Faulkes telescopes. Within the context of the standard fireball model, we rule out a reverse shock origin for the early time optical emission in GRB 090727 and instead conclude that the early time optical flash likely corresponds to emission fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
40
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 130 publications
2
40
0
Order By: Relevance
“…A first indication of the internal or external origin of the early-time optical emission comes from its temporal behaviour, which is expected to track the variability that is detected in the hard X-ray band when the two share a common internal origin. These different behaviours have in-deed been pointed out in the study of prompt optical emission, and have shown that its origin is not always the same and can vary for each case (see Kopač et al 2013 for a recent systematic investigation).…”
Section: Introductionmentioning
confidence: 97%
“…A first indication of the internal or external origin of the early-time optical emission comes from its temporal behaviour, which is expected to track the variability that is detected in the hard X-ray band when the two share a common internal origin. These different behaviours have in-deed been pointed out in the study of prompt optical emission, and have shown that its origin is not always the same and can vary for each case (see Kopač et al 2013 for a recent systematic investigation).…”
Section: Introductionmentioning
confidence: 97%
“…Bright optical flashes are now ruled out by observations in many events, while other events show complicated optical light curves that, like the prompt γ-ray emission, may originate instead from internal shocks (Kopač et al 2013;Japelj et al 2014). Some authors have proposed that RS emission may be easier to observe at longer wavelengths, where the emission peaks on timescales of days (Mundell et al 2007;Melandri et al 2010;Kopač et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the overall success of this framework, the prompt emission mechanism is still poorly known, and internal shocks remain an inefficient mechanism for the conversion of kinetic to radiated energy (e.g., Beloborodov 2005;Rees & Mészáros 2005;Zhang & Yan 2011;Axelsson & Borgonovo 2015;Beniamini et al 2015). In addition, although the generally accepted external shock model works well for smoothly fading late time (∼ days post burst) afterglows, observations of early afterglow light curves in the first minutes to hours after the burst, especially in the era of the Swift satellite (Gehrels et al 2004), show an unexpected wealth of variety, attributed to a range of mechanisms including internal and external shocks, long-lived central engines and double jet structures (e.g., Monfardini et al 2006;Mundell et al 2007b;Gomboc et al 2008;Melandri et al 2008Melandri et al , 2010Virgili et al 2013;Kopač et al 2013;Japelj et al 2014;de Pasquale et al 2015).…”
Section: Introductionmentioning
confidence: 99%